> 数学 >
求证 sin^2x/(sinx-cosx)-(sinx+cosx)/tan^2 x-1=sinx+cosx
人气:298 ℃ 时间:2020-02-04 04:16:54
解答
左边=sin²x/(sinx-cosx)-(sinx+cosx)/(sin²x/cos²x-1)
=sin²x(sinx+cosx)/(sinx-cosx)(sinx+cosx)-(sinx+cosx)cos²x/(sin²x-cos²x)
=(sin³x+sin²xcosx-sinxcos²x-cos³x)/(sinx+cosx)(sinx-cosx)
=[(sinx-cosx)(sin²x+sinxcosx+cos²x)+sinxcosx(sinx-cosx)/(sinx+cosx)(sinx-cosx)
=(sinx-cosx)(sin²x+2sinxcosx+cos²x)/(sinx+cosx)(sinx-cosx)
=(sinx-cosx)(sinx+cos)²/(sinx+cosx)(sinx-cosx)
=sinx+cosx=右边
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版